2012
DOI: 10.1016/j.dld.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional aspects of distal oesophageal spasm: The role of onset velocity and contraction amplitude on bolus transit

Abstract: Background Distal oesophageal spasm (DES) is a rare and under-investigated motility abnormality. Recent studies indicate effective bolus transit in varying percentages of DES patients. Aim Explore functional aspects including contraction onset velocity and contraction amplitude cut-off values for simultaneous contractions to predict complete bolus transit Methods We re-examined data from 107 impedance-manometry recordings with a diagnosis of DES. Receiver operating characteristic (ROC) analysis was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Using combined impedancemanometry additional data about esophageal motor function and associated bolus transport can be obtained during a single investigation without the use of radiation [22] Savarino et al showed a correlation between esophageal motor abnormalities and bolus transit defects in different subcategory of GERD patients [23]. Moreover, Pohl D et al proposed a bolus velocity cut-off in diagnosing patients with esophageal spasm and abnormal bolus transit [24].…”
Section: Esophageal Physiologymentioning
confidence: 99%
“…Using combined impedancemanometry additional data about esophageal motor function and associated bolus transport can be obtained during a single investigation without the use of radiation [22] Savarino et al showed a correlation between esophageal motor abnormalities and bolus transit defects in different subcategory of GERD patients [23]. Moreover, Pohl D et al proposed a bolus velocity cut-off in diagnosing patients with esophageal spasm and abnormal bolus transit [24].…”
Section: Esophageal Physiologymentioning
confidence: 99%